Proteomic analysis of Chromobacterium violaceum and its adaptability to stress - Castro, Diogo; Cordeiro, Isabelle Bezerra; Taquita, Paula; Eberlin, Marcos Nogueira; Garcia, Jerusa Simone; Souza, Gustavo Henrique M. F.; Arruda, Marco Aurélio Zezzi; Andrade, Edmar V.; Filho, Spartaco A.; Crainey, J. Lee; Lozano, Luis Lopez; Nogueira, Paulo A.; et al. (BMC microbiology, 2015)
Chromobacterium violaceum (C. violaceum) occurs abundantly in a variety of ecosystems, including ecosystems that place the bacterium under stress. This study assessed the adaptability of C. violaceum by submitting it to nutritional and pH stresses and then analyzing protein expression using bi-dimensional electrophoresis (2-DE) and Maldi mass spectrometry. Chromobacterium violaceum grew best in pH neutral, nutrient-rich medium (reference conditions); however, the total protein mass recovered from stressed bacteria cultures was always higher than the total protein mass recovered from our reference culture. The diversity of proteins expressed (repressed by the number of identifiable 2-DE spots) was seen to be highest in the reference cultures, suggesting that stress reduces the overall range of proteins expressed by C. violaceum. Database comparisons allowed 43 of the 55 spots subjected to Maldi mass spectrometry to be characterized as containing a single identifiable protein. Stress-related expression changes were noted for C. violaceum proteins related to the previously characterized bacterial proteins: DnaK, GroEL-2, Rhs, EF-Tu, EF-P; MCP, homogentisate 1,2-dioxygenase, Arginine deiminase and the ATP synthase β-subunit protein as well as for the ribosomal protein subunits L1, L3, L5 and L6. The ability of C. violaceum to adapt its cellular mechanics to sub-optimal growth and protein production conditions was well illustrated by its regulation of ribosomal protein subunits. With the exception of the ribosomal subunit L3, which plays a role in protein folding and maybe therefore be more useful in stressful conditions, all the other ribosomal subunit proteins were seen to have reduced expression in stressed cultures. Curiously, C. violeaceum cultures were also observed to lose their violet color under stress, which suggests that the violacein pigment biosynthetic pathway is affected by stress. Analysis of the proteomic signatures of stressed C. violaceum indicates that nutrient-starvation and pH stress can cause changes in the expression of the C. violaceum receptors, transporters, and proteins involved with biosynthetic pathways, molecule recycling, energy production. Our findings complement the recent publication of the C. violeaceum genome sequence and could help with the future commercial exploitation of C. violeaceum.